The Association of Retinol-Binding Protein 4 With Metabolic Syndrome and Obesity in Adolescents: The Effects of Gender and Sex Hormones. (January 2013) - Lin, Chin-Jung; Chu, Nain Feng; Hung, Yi-Jen; Chang, Jin-Biou; He, Chih-Tsueng; Hsiao, Fone-Ching; Hsieh, Chang-Hsun
Objectives . Retinol-binding protein 4 (RBP4) has a role in the development of insulin resistance (IR), type 2 diabetes, obesity, and metabolic syndrome among adults. However, data among adolescents are limited, and the effects of gender and sex hormones on RBP4 are not well defined. Materials/Methods . A total of 1082 adolescents were enrolled and categorized based on their body mass index. Blood samples were collected, and biochemical characteristics, sex hormones, RBP4 concentrations, and IR were determined. Results . Testosterone and estradiol were not directly correlated with RBP4 concentrations in both genders. Multivariate regression analysis revealed that fasting plasma glucose (FPG), triglyceride (TG), and testosterone levels were independently associated with RBP4 concentrations in boys; also, there was a trend of increasing RBP4 levels with the severity of obesity. Conclusion . Plasma RBP4 concentrations correlated with obesity and cardiovascular risk factors, predominantly evident in boys. Testosterone, FPG, and TG levels were independent predictors of RBP4 concentrations.